ABU YUSUF'S THOUGHTS ON ISLAMIC ECONOMICS - Rosana, Mayang (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
In studying the history of Islamic economic thought in particular and the history of Islamic thought in general, it is necessary to straighten back and convey a historical fact of emergence, development, and policy. To deepen the study of the history of modern Islamic economic thought, it must also examine the previous economic figures. It is their economic thinking that has contributed to the current scientific repertoire of Islamic economics. One of the earliest economic figures who was brilliant in his time was Abu Yusuf who was famous for his book Kharaj during the time of Caliph Harun al-Rashid. This paper discusses the thoughts of Abu Yusuf, who was very concentrated on efforts to realize the welfare of the people. This paper starts from Abu Yusuf's biography, his works, then discusses thoughts on Islamic economics at the time of Abu Yusuf. The type of research used is descriptive qualitative literature research. The result of this research is Abu Yusuf has the full name Ya'qub bin Ibrahim bin Habib Khunais Bin Sa'ad al-Anshari al-Jalbi al-Kufi al-Baghdadi. During his lifetime Abu Yusuf had many works, such as kitab al-atsar, kitab Ikhtilaf Abi Hanifah wa Ibn Abi Laila, kitab ar-radd 'ala siyar al-auza'I, and kitab al-kharaj. Of some of his works, the most famous is the book of al-kharaj. Abu Yusuf's thought is in the form of state economic thought, which explores fiscal policy, which deals with state revenue. This can be seen from the content of his thoughts that map the mechanism of state revenue, expenditure detailed in Incidental Income, Permanent Income and several aspects that are closely related to government policy.